The Regional Supervision and Cancellation Mechanism - Yunita Bahar; Armansyah; Mirza (Polit Journal Scientific Journal of Politics, 2021)
The amendment to Law Number 32 of 2004 to Law Number 23 of 2014 concerning Regional Government further emphasizes the centralized relationship between the central government and regional governments, which during post-independence experienced high dynamics, especially in terms of the concept of domination of power between the two. One of the significant impacts of this change lies in the central government's supervisory authority over regional regulations established by regional governments. This condition further strengthens the position of the central government towards regional governments. On the one hand, it reinforces the concept of a unitary state, but, on the other hand, further limits the authority of local governments in implementing regional autonomy. Both are mandates of the 1945 Constitution. The supervisory authority also has an impact on the authority to cancel regional regulations by the central government. This can not only be seen from the aspect of the relationship between the central and local governments, but also relates to the perspective of legislation. With the cancellation, it is important to look at the available legal remedies if there are those who are not happy with the implementation of the cancellation authority.